2014
DOI: 10.1002/cne.23701
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐specific and developmental expression of lectican‐cleaving proteases in mouse hippocampus and neocortex

Abstract: Mounting evidence has demonstrated that a specialized extracellular matrix exists in the mammalian brain, and this glycoprotein-rich matrix contributes to many aspects of brain development and function. The most prominent supramolecular assembly of these ECM glycoproteins are perineuronal nets, specialized lattice-like structures that surround the cell bodies and proximal neurites of select classes of interneurons. Perineuronal nets are composed of lecticans – a family of chondroitin sulfate proteoglycans [CSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 99 publications
4
33
0
Order By: Relevance
“…Our data revealed ADAMTS‐4 as present in the white matter of the CNS, only in mature APC positive oligodendrocytes. These data are in agreement with recent studies that have reported the expression of ADAMTS‐4 in mature oligodendrocytes by in situ hybridization in the developing telencephalon (Levy, Brooks, Chen, Su, & Fox, ) and by immunohistochemistry of adult mouse spinal cord (Lemarchant, Pomeshchik, et al, ). Notably, ADAMTS‐4 protein was recently described as highly enriched in oligodendrocytes by a proteomic analysis (Sharma et al, ), among the well‐known oligodendrocytes proteins such as MBP, PLP, 2′,3′‐cyclic nucleotide 3′‐phosphodiesterase and the transcription factor Sox10.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data revealed ADAMTS‐4 as present in the white matter of the CNS, only in mature APC positive oligodendrocytes. These data are in agreement with recent studies that have reported the expression of ADAMTS‐4 in mature oligodendrocytes by in situ hybridization in the developing telencephalon (Levy, Brooks, Chen, Su, & Fox, ) and by immunohistochemistry of adult mouse spinal cord (Lemarchant, Pomeshchik, et al, ). Notably, ADAMTS‐4 protein was recently described as highly enriched in oligodendrocytes by a proteomic analysis (Sharma et al, ), among the well‐known oligodendrocytes proteins such as MBP, PLP, 2′,3′‐cyclic nucleotide 3′‐phosphodiesterase and the transcription factor Sox10.…”
Section: Discussionsupporting
confidence: 92%
“…The major finding of our present study is that the extracellular ADAMTS-4, initially characterized in the cartilage (Tortorella et al, 1999) is exclusively expressed by myelinating oligodendrocytes in the normal CNS, influences myelination processes, axonal conduction and finally motor performances. (Levy, Brooks, Chen, Su, & Fox, 2015) and by immunohistochemistry of adult mouse spinal cord . Notably, ADAMTS-4 protein was recently described as highly enriched in oligodendrocytes by a proteomic analysis (Sharma et al, 2015), among the well-known oligodendrocytes proteins such as MBP, PLP, 2 0 ,3 0 -cyclic nucleotide 3 0 -phosphodiesterase and the transcription factor Sox10.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue inhibitors of metalloproteinases (TIMPs) inhibit matrix metalloproteinases (MMPs) as well as the closely related ‘A Disintegrin and Metalloprotease’ (ADAMs) and ADAMs with thrombospondin motifs (ADAMTSs), all of which are involved in ECM proteolysis (Arpino et al, 2015; Levy et al, 2015; Pizzi and Crowe, 2007; Seals and Courtneidge, 2003; Senkov et al, 2014). Therefore, PNN stability in response to Pavlovian fear conditioning could be influenced by the activity and expression of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…However, several previous studies had also strongly suggested that ADAMTS4 could be an oligodendrocyte-specific gene. First, an in situ hybridization study had detected ADAMTS4 mRNA specifically in oligodendrocytes of the mouse hippocampus and cortex at P21, and in co-localization studies the riboprobe only bound to cells positive for the oligodendrocyte marker Olig2 [44]. Second, a state-of-the-art transcriptome study of all major brain cell types had indicated that ADAMTS4 is specifically expressed in oligodendrocytes [82].…”
Section: Discussionmentioning
confidence: 99%